2011
DOI: 10.1007/s10336-011-0707-0
|View full text |Cite
|
Sign up to set email alerts
|

Early development, recruitment and life history trajectory in long-lived birds

Abstract: International audienceLindström (in Trends Ecol Evol 14:343-347, 1999) synthesized knowledge about "early development and fitness in birds and mammals", interesting tracks and challenges for future studies. Today, there is unambiguous evidence that Lindström's first statement holds in long-lived birds: "It is obvious that adverse environmental conditions might have immediate effects [...]." However, whether there are "long-term fitness consequences of conditions experienced during early development" (Lindström… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 195 publications
(264 reference statements)
2
69
0
Order By: Relevance
“…However, it is still unclear whether the difference between breeders and nonbreeders is because of intrinsic quality of birds ('individual quality hypothesis') [22]-which can be determined by nutritional histories of individuals during development (at least partially addressed in this study), genetic/epigenetic factors or arise from learned behaviour-or reflects dynamic accumulation of fitness differences [61]. Although this is an important question, long-term monitoring programmes are needed to address it, preferably those focusing on complete reproductive histories and longevity of individuals, multi-generational effects and considering migrants from other colonies.…”
Section: (F ) Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still unclear whether the difference between breeders and nonbreeders is because of intrinsic quality of birds ('individual quality hypothesis') [22]-which can be determined by nutritional histories of individuals during development (at least partially addressed in this study), genetic/epigenetic factors or arise from learned behaviour-or reflects dynamic accumulation of fitness differences [61]. Although this is an important question, long-term monitoring programmes are needed to address it, preferably those focusing on complete reproductive histories and longevity of individuals, multi-generational effects and considering migrants from other colonies.…”
Section: (F ) Future Workmentioning
confidence: 99%
“…Although understanding reproductive dynamics is central for understanding the basic and applied ecology of long-lived seabirds, we still have limited knowledge about factors affecting age at recruitment, reproductive effort and nesting habitat selection [20,21]. In particular, whether early conditions have long-term consequences on life-history strategies remains ambiguous [22], in part, because of few longitudinal studies with the power to examine these issues (studies investigating the interaction between developmental and adult environments [9]). …”
Section: Introductionmentioning
confidence: 99%
“…The period of animal development prior to maturity can have important effects on an individual's fitness (Cam and Aubry, 2011;Cam et al, 2003;Desai and Hales, 1997;DuRant et al, 2013;Lindström, 1999;Metcalfe and Monaghan, 2001). The environmental conditions experienced at these early life stages may affect growth and survival prior to independence (Burness et al, 2000;de Kogel, 1997;Gebhardt-Henrich and Richner, 1998;Green and Cockburn, 2001;Haywood and Perrins, 1992), adult phenotype (Boag, 1987;de Kogel, 1997;de Kogel and Prijs, 1996), survival prior to recruitment as a breeder (Cam et al, 2003;Magrath, 1991), age at recruitment (Cam et al, 2003), reproductive fitness (Haywood and Perrins, 1992;Schluter and Gustafsson, 1993), and even adult survival (Albon et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Poor-quality natal environments frequently have negative short-term effects on fitness components such as juvenile body condition and juvenile survival (Magrath 1991, van der Jeugd and Larsson 1998, van de Pol et al 2006. In recent years, however, a growing body of literature has indicated that favorable conditions in the natal environment can have significant long-term fitness benefits (Lindström 1999, Cam andAubry 2011). These delayed ''silver spoon'' effects (Grafen 1988) are manifested in later life stages and can affect an array of fitness components, including dispersal and habitat selection (Stamps 2006, van de Pol et al 2006, Tilgar et al 2010, Tarwater and Beissinger 2012, phenotypic characters under sexual selection (Scandolara et al 2014), clutch and litter size (Tilgar et al 2010, Rödel et al 2009), and lifetime reproductive performance (Cam et al 2003).…”
Section: Introductionmentioning
confidence: 99%